THE EFFECT OF THE COMBINATION OF N, P, K AND BIOLOGICAL FERTILIZERS TO THE GROWTH AND YIELD OF RED ONION ON ALLUVIAL SOILS - Saputra, Danu; Anggorowati, Dini; Rahayu, Sri (Jurnal Sains Pertanian Equator, 2020)
This study aims to determine the combination dose of N, P, K and biological fertilizers on the growth and yield of red onion in alluvial soils. This research was conducted in the experimental field of the Faculty of Agriculture, Tanjungpura University, Pontianak, which took place on April 19, 2019 until June 23, 2019. The method used was a Completely Randomized Design (CRD) consisting of 5 treatments, 5 replications, and 4 sample plants. Giving a combination of N, P, K and biological fertilizer that is A1 100% N, P, K + 0% biological, A2 75% N, P, K + 25% biological, A3 50% N, P, K + 50% biological , A4 25% N, P, K + 75% biological, A5 0% N, P, K + 100% biological. Observations made were the number of leaves, plant height, number of tubers, fresh weight of tubers, and dry weight of tubers. The results showed that the combination of N, P, K and biological fertilizers significantly affected the variable number of leaves, plant height, fresh weight of tubers and dry weight of tubers but had no significant effect on the observed variables of number of tubers. Based on the results during the study it can be concluded that the administration of a combination of 50% N, P, K fertilizer and 50% biological fertilizer is a more effective dose than other doses for growth and yield of shallots in alluvial soils. Keywords : Red Onion, NPK Fertilizer, Biofertilizer, Alluvial.